PENINGKATAN MUTU PENDIDIKAN MELALUI KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH, MANAJEMEN BERBASIS SEKOLAH, DAN KETERLIBATAN KERJA GURU DI MADRASAH ALIYAH SWASTA KECAMATAN PONDOK AREN KOTA TANGERANG SELATAN - Ahmad Tarmuji; Siti Zubaidah; Herdi Wisman Jaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effects of transformational leadership of madrasah principals, School-Based Management, and teacher work engagement on educational quality in private Madrasah Aliyah (Islamic senior high schools) in Pondok Aren District, South Tangerang City, both partially and simultaneously. The study employed a quantitative approach using a survey method with an associative research design. The population consisted of 143 teachers from five private Madrasah Aliyah, with a sample of 105 teachers determined using the Slovin formula at a 5% margin of error. Data were collected through a validated and reliable Likert-scale questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics. The results indicated that transformational leadership of madrasah principals had a positive and significant effect on educational quality (β = 0.394; t = 6.646), School-Based Management also had a positive and significant effect (β = 0.239; t = 4.686), and teacher work engagement positively and significantly influenced educational quality (β = 0.178; t = 3.183). Simultaneously, the three independent variables had a positive and significant effect on educational quality (F = 391.664; p < 0.001), with a coefficient of determination (R²) of 0.921, indicating that 92.1% of the variance in educational quality was explained by the three variables. Transformational leadership of madrasah principals was identified as the most dominant predictor of educational quality. These findings highlight the importance of strengthening transformational leadership, optimizing the implementation of School-Based Management, and enhancing teacher work engagement as strategic efforts to improve educational quality in madrasahs.